ANALISIS PENYERAPAN TENAGA KERJA DI KABUPATEN TIMUR TENGAH SELATAN PROPINSI NUSA TENGGARA TIMUR - Tomasowa, Olivia Louise Eunike; Kaluge, David (Journal of Innovation in Business and Economics, 2012)
The research is analyzing the absorption of workers at TTS East Nusa Tenggara Province in period 2005-2010. Research aims at: identifying sectors with the strength of absorbing workers in period 2005-2010; understanding the output produced by sector workers at TTS; and acknowledging how is the effect of the economic growth on the absorption of workers at TTS in period 2005-2010. Analysis tools are Location Quotient (LQ), TK Productivity, TK Elasticity, MRP, and Klassen Typology. Result of research indicates that mining and quarring sector, and electricity, gas and water sectors are superior sectors in absorbing workers.